Re-Branding of Aceh: Islamic Public Space Contestation, Special Autonomy and New Strategies - Fathayatul Husna (UIN Sulthan Thaha Saifuddin Jambi, 2022)
Aceh is well known as a region that applies Islamic law as a whole. Times have brought about the intake of social changes which also have an influence on the social order of religion in Aceh. researcher examined through two main conditions, before and after special autonomy legitimation. This theme should to be examined because researcher argue there is Islamic content development in Aceh public space. This paper examines the Islamic public sphere in Aceh as an area with Islamic legitimacy. the author wants to see how the discourse on Islamic public space after the development of technology at the same time and after the conflict. This type of research is descriptive qualitative. The author uses a virtual ethnography method. The result that the authors get is that the Islamic public sphere in Aceh has changed between before the special autonomy was passed and after the special autonomy. Obviously, the development of the Islamic public space in Aceh has been fed by technological developments after the.